Carbohydrate Concentration Influences on In Vitro Plant Regeneration in Stevia rebaudiana - C.V. Naidu, D. Preethi1, T.M. Sridhar1 and (Journal of Phytology, 2011)
In the present study effect of various carbon sources such as sucrose, glucose, fructose and maltose was investigated on in vitro shoot regeneration of Stevia rebaudiana using nodal explants. The frequency, growth and multiplication rate were highly influenced by the type and concentration of carbon sources used.Ã‚Â The highest number of shoots (21.4Ã‚Â±0.80), shoot length (5.36Ã‚Â±0.55) was obtained on MS medium supplemented with 4% fructose.Ã‚Â The least number of shoots (1.3Ã‚Â±0.47) was obtained on 6% glucose and the least shoot length (1.22Ã‚Â±0.25) was observed on 1% sucrose.Ã‚Â Among the different carbon sources used in the present study, fructose at 4% proved to be better choice for multiple shoot regeneration followed by sucrose, maltose and glucose, from nodal explants of Stevia rebaudiana.